Reply to Chang et al., 2014, Evolution of the South China Sea: Revised ages for breakup and seafloor spreading. (January 2015) - Barckhausen, Udo; Engels, Martin; Franke, Dieter; Ladage, Stefan; Pubellier, Manuel
Abstract: Chang et al. introduce some new lines of evidence for an end of seafloor spreading in the South China Sea not before 15 Ma. However, we find strong indications that their interpretation is not conclusive. The origin of the East Taiwan Ophiolite from the SCS as assumed by Chang et al. is not in agreement with recent studies which find continental crust in the deep-water domain of the northeastern South China Sea. The age dating of the East Taiwan Ophiolite is based on one single K–Ar age of questionable accuracy. The calculation of Te-derived ages leaves a thermal rejuvenation of the oceanic crust in the South China Sea by post-spreading volcanism out of consideration. Biostratigraphically determined ages of sediments recovered directly above igneous crust of the South China Sea during IODP 349 drilling expedition are inconclusive so far. The final key to unlocking the spreading history of the SCS will be the Ar–Ar age dating of the basaltic rocks recovered during IODP Expedition 349.